High body mass index is associated with heightened systemic and mycobacterial antigen – Specific pro-inflammatory cytokines in latent tuberculosis. (December 2016) - Anuradha, Rajamanickam; Munisankar, Saravanan; Bhootra, Yukthi; Dolla, Chandrakumar; Kumaran, Paul; Babu, Subash
Summary: High body mass index (HBMI) has been shown to be protective against active tuberculosis (TB), although the biological mechanism underlying this protection is poorly understood. The immunological association between HBMI and latent TB has never been examined. In order to study the association of HBMI with latent TB, we examined the circulating and TB- antigen or mitogen stimulated levels of a large panel of cytokines in individuals with latent TB (LTB) and high or normal body mass index (HBMI or NBMI). HBMI is characterized by heightened circulating levels of pro-inflammatory (IFNγ, TNFα, IL-22, IL-1α, IL-12 and GM-CSF) cytokines but decreased circulating levels of anti-inflammatory cytokines (IL-4, IL-5 and TGFβ). This systemic cytokine profile is associated with elevated TB-antigen and mitogen stimulated levels of IFNγ, TNFα, IL-2 and IL-1α and diminished levels of IL-10 and TGFβ. In addition, we also observed a positive correlation between the circulating levels of IFNγ, TNFα, IL-22, IL-1α with BMI and a negative correlation between the circulating levels of IL-10, TGFβ and BMI. Our data, therefore, suggest the modulation of protective and regulatory cytokines might underlie the protective effect of HBMI against the development of active TB.